ENERGY SAVINGS AND SPEED IMPROVEMENT IN LINEAR POWER HYDRAULIC ACTUATORS USING A SELF-ACTUATED FLOW CONTROL VALVE - MOHAMED, MOHAMED OSMAN ABDALLA (2013)
This research concerns the energy efficiency and speed improvement in the hydraulic actuation system. Energy saving potentials in both the spool valves and the hydraulic cylinders were investigated in the FLUENT code. The probable sources of energy losses in these components were explored and the solutions were proposed. The spool valve was optimised and improved by the elimination of sharp comers and flow restrictions in the valve. Different geometrical modifications have been proposed and simulated. Modification of the spool body geometry and the inlet port geometry showed very little improvement. While the modification of the outlet port geometry with conical surfaces, and showed good improvement regarding the pressure loss.